THE ROLE OF RELIGIOUS LEADERS IN SHAPING THE CHARACTER EDUCATION OF DILIGENT WORSHIP IN ADOLESCENTS IN KEDAI DURIAN VILLAGE DELI SERDANG DISTRICT - Aqilah Faiza, Adzro; Putra Dinata Saragi, Muhammad (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The purpose of this study was to determine the role of religious leaders in shaping character education diligent worship in adolescents, as well as supporting and inhibiting factors in shaping character education diligent worship in adolescents. The research method used is qualitative method. Islamic religious leaders in this case are Islamic religious instructors of KUA Delitua Subdistrict, ustadz, and Islamic religious education teachers who live in Kedai Durian Village. Respondents of this study were obtained using purposive sampling technique. The data collection techniques used were interviews, observation, and documentation. The data analysis technique used was data reduction. The results showed that religious leaders act as educators who provide education to teenagers, provide information, defence, and become consultants in terms of teenage worship. The methods used are lectures, special guidance, and giving examples of actions. Supporting factors are positive feedback from adolescents, the enthusiasm and motivation of adolescents in terms of studying, as well as support from parents and the presence of youth Islamic organisations in Kedai Durian Village. While the inhibiting factors are the unstable condition of adolescents, the times that have a negative influence on the practice of teenage worship, and the indifference of parents to the efforts made by religious leaders in shaping character education diligent worship in adolescents. So it can be concluded that there needs to be a positive response and cooperation between religious leaders and the entire community, both teenagers and parents, so that the formation of character education for diligent worship in adolescents runs as expected.